Financial Development, Financial Fragility, and Growth - Norman Loayza; Romain Ranciere (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper attempts to reconcile the apparent contradiction between two strands of the literature on the effects of financial intermediation on economic activity. On the one hand, the empirical growth literature finds a positive effect of financial depth as measured by, for instance, private domestic credit and liquid liabilities (e.g., Levine, Loayza, and Beck 2000). On the other hand, the banking and currency crisis literature finds that monetary aggregates, such as domestic credit, are among the best predictors of crises and their related economic downturns (e.g., Kaminski and Reinhart 1999). This paper starts by illustrating these opposing effects by, first, analyzing the dynamics of output growth and financial intermediation around systemic banking crises and, second, showing that the growth enhancing effects of financial depth are weaker in countries that experienced such crises. After these illustrative exercises, the paper attempts an empirical explanation of the apparently opposing effects of financial intermediation. This explanation is based on a distinction between transitory and trend effects of domestic credit aggregates on economic growth. Working with a panel of cross-country and time-series observations, the paper estimates an encompassing model of long- and short-run effects, following Pesaran, Shin, and Smith (1999)'s Pooled Mean Group Estimator. The main result of the paper is that a positive long-run relationship between financial intermediation and output growth co-exists with a, mostly, negative short-run relationship.
Keywords: 330